2016
DOI: 10.1097/mib.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Vaccine Response in Inflammatory Bowel Disease Patients on Low-dose Immunosuppression

Abstract: IBD patients on low-dose immunosuppressive therapy have a blunted immune response to HZV as compared with nonimmunosuppressed subjects. Despite this, immunosuppressed IBD patients are able to mount a statistically significant immune response. There were no serious adverse events to HZV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The UK Department of Health Green Book vaccination guide Chapter 6730 also suggests that all live vaccines can be considered for those on low-dose immunosuppression as defined above, including low-dose immunosuppressive drugs in combination with prednisolone up to 20 mg. There is evidence from a small controlled study that the use of zoster vaccine in IBD patients on low-level immunosuppression does not result in adverse effects, although antibody titres were somewhat lower than those in vaccinated IBD patients not taking immunosuppressive drugs 736. Live vaccination must not be given to those taking biologics, and should only be undertaken for those on low-level immunosuppression after careful consideration of the risks and benefits in conjunction with the patient.…”
Section: Common Disease Considerationsmentioning
confidence: 99%
“…The UK Department of Health Green Book vaccination guide Chapter 6730 also suggests that all live vaccines can be considered for those on low-dose immunosuppression as defined above, including low-dose immunosuppressive drugs in combination with prednisolone up to 20 mg. There is evidence from a small controlled study that the use of zoster vaccine in IBD patients on low-level immunosuppression does not result in adverse effects, although antibody titres were somewhat lower than those in vaccinated IBD patients not taking immunosuppressive drugs 736. Live vaccination must not be given to those taking biologics, and should only be undertaken for those on low-level immunosuppression after careful consideration of the risks and benefits in conjunction with the patient.…”
Section: Common Disease Considerationsmentioning
confidence: 99%
“…33,34 It has also been shown that the immunological response to vaccination is sometimes decreased in patients exposed to immunosuppressive therapy. [35][36][37] How to treat IBD after a serious infection…”
Section: What Type Of Vaccine For Which Type Of Patients?mentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) suggest that vaccination is safe for those patients receiving low-dose immunosuppression (<20 mg/d of prednisone or equivalent), 61 although other studies have shown a dimimished antibody response to the LZV in patients on low-dose immunosuppressive therapy. 68 HZ vaccination in patients with IBD taking anti-TNF medication has now been shown to be relatively safe. 69 Due to the potential for prolonged viremia, a period of time between vaccination and immunosupression could theoretically decrease the risk of reactivation.…”
Section: Prevention Of Hzmentioning
confidence: 99%